2010
DOI: 10.1111/j.1463-1318.2010.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal cancer surgery in obese patients

Abstract: Laparoscopic colorectal cancer surgery in obese patients is technically feasible and oncologically safe. Despite greater postoperative morbidity, obese patients benefit from shorter length of stay. However, a higher conversion rate, particularly for rectal cancers, should be anticipated in obese male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 22 publications
1
96
1
Order By: Relevance
“…Zou et al [25] reported that obesity was associated with increased wound infection, ileus, incisional hernia, and with pulmonary events. The incidence of wound infection seen in obese patients in our study, which was similar to that in other studies [26,27], was significantly higher than that in non-obese patients (8.3% vs 1.9%).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Zou et al [25] reported that obesity was associated with increased wound infection, ileus, incisional hernia, and with pulmonary events. The incidence of wound infection seen in obese patients in our study, which was similar to that in other studies [26,27], was significantly higher than that in non-obese patients (8.3% vs 1.9%).…”
Section: Discussionsupporting
confidence: 77%
“…However, these results were based on the short-term outcomes of laparoscopic colorectal surgery. Several investigators have studied the long-term prognostic outcomes after laparoscopic colorectal cancer surgery in obese patients [26] [34]. No statistically significant differences were observed between the obese and non-obese patients in terms of the disease-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 However, several studies have shown that there were no significant differences in survival between obese and non-obese Western patients. 5,22 To our knowledge, few studies have examined long-term surgical outcomes following laparoscopic colorectal cancer in Asian patients. The results of this study showed no significant differences in disease-free and overall survival between obese and non-obese patients in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…56 Short-term morbidity for rectal cancer resection seems to be increased with obesity. In addition, obesity is reported to be significantly associated with rates of anastomotic leak, 57,58 parastomal hernia, 59 wound infection, 60,61 length of laparoscopic surgery according to BMI, [46][47][48]60 length of laparoscopic surgery according to visceral adipose area, 62,63 overall and systemic complications, 62 more frequent conversion to laparotomy, 46,64 more blood loss, 47,58,63 and longer hospital stay. 48 In addition, obese patients undergoing laparoscopic colorectal surgery are at an increased risk for conversion to open operation and operative times are significantly increased for obese patients having rectal cancer surgery.…”
Section: Obesity and Colorectal Surgery Outcomesmentioning
confidence: 99%